(untitled) (APPLICATION: Applied science in Learning Research, 2021)
This research aims to design ‘Gring- Med’ Grammar Learning Media which it focused on intermediate students in learning English at school. The research method used a Research and Development (R&D) method with using ADDIE model, this model consists of five sections which are analysis, design, development, implementation, and evaluation. There are two validation of the feasibility of this product media. First, validation of materials, and the second is validation of media. Both of them have validated by each experts validator before trying to the students. The data collection was carried out using a questionnaire. The result of implementation are in the form of an assessment of student work and suggestion of media Gring- Med. The result of implementation indicate that the acquisition average percentage of the assessment is 88,3% in the ‘very good’ category. So, based on the result of this research, it can be conclude that Gring-Med application of grammar learning media is suitable to help the students grade X of MA Al – Asy’ari.